Can postbiotics show antiviral effects against Sars-CoV-2? (Research, Society and Development, 2021)
Severe Acute Respiratory Syndrome of Coronavirus-2 (Sars-CoV-2) is the causative agent of the new Coronavirus Disease (COVID-19) responsible for the current pandemic that threatens global health. Although some anti-COVID-19 therapeutic agents are under investigation, there is still no evidence of antiviral action against Sars-CoV-2. Research in the literature describes the success of probiotics in the treatment of viral infections from their byproducts, known as postbiotics, such as exopolysaccharides, hydrogen peroxide, and different bacteriocins. Based on these reports, we describe the main postbiotics that present antiviral actions against different viruses with a view to suggesting their use as possible therapeutic agents for COVID-19. The revised data show promising effects for using postbiotics as efficient vehicles against various types of viruses. However, further investigation of the underlying mechanisms is required for their indication against Sars-CoV-2 and other Sars-CoV infections.